The Policing and Prosecution of Rape: What Do We Know and How Should Our Knowledge Shape Policy and Practice? - Stanko, with Louise Ellison, Martin Hewitt and Harriet Wistrich, Betsy (feminists@law, 2014)
This is a video of a lecture given by Betsy Stanko at LSE on 11 March 2014, in which she presents the findings of her research on the investigation and prosecution of rapes reported to the Metropolitan Police Service over the 8 years from 2005-2013. The lecture is followed by comments from panellists Louise Ellison, Martin Hewitt and Harriet Wistrich. Louise Ellison addresses the treatment of rape complainants with mental health conditions; Martin Hewitt discusses the need to provide access to justice for rape victims; and Harriet Wistrich talks about the recent civil case, DSD v Commissioner of Police for the Metropolis [2014] EWHC 436 (QB), in which two of the victims of serial rapist John Worboys successfully sued the Metropolitan Police under the Human Rights Act 1998 for failures in their investigation of the rapes. The event was organised by LSE Law, LSE Gender Institute and the Mannheim Centre for Criminology, and was chaired by Christine Chinkin.